Subsets of exhausted CD8+ T cells differentially mediate tumor control and respond to checkpoint blockade - Miller, Brian C.; Sen, Debattama R.; Al Abosy, Rose; Bi, Kevin; Virkud, Yamini V.; LaFleur, Martin W.; Yates, Kathleen B.; Lako, Ana; Felt, Kristen; Naik, Girish S.; Manos, Michael; Gjini, Evisa; et al. (Nature immunology, 2019)
T cell dysfunction is a hallmark of many cancers, but the basis for T cell dysfunction and the mechanisms by which antibody blockade of the inhibitory receptor PD-1 (anti-PD-1) reinvigorates T cells are not fully understood. Here we show that such therapy acts on a specific subpopulation of exhausted CD8 + tumor-infiltrating lymphocytes (TILs). Dysfunctional CD8 + TILs possess canonical epigenetic and transcriptional features of exhaustion that mirror those seen in chronic viral infection. Exhausted CD8 + TILs include a subpopulation of ‘progenitor exhausted’ cells that retain polyfunctionality, persist long term and differentiate into ‘terminally exhausted’ TILs. Consequently, progenitor exhausted CD8 + TILs are better able to control tumor growth than are terminally exhausted T cells. Progenitor exhausted TILs can respond to anti-PD-1 therapy, but terminally exhausted TILs cannot. Patients with melanoma who have a higher percentage of progenitor exhausted cells experience a longer duration of response to checkpoint-blockade therapy. Thus, approaches to expand the population of progenitor exhausted CD8 + T cells might be an important component of improving the response to checkpoint blockade. Exhausted cytotoxic T lymphocytes (CTLs) express the receptor PD-1 as a key signature. Haining and colleagues show that there are different ‘depths’ of exhaustion with a subset of exhausted CTLs that retain polyfunctionality and are responsive to PD-1 blockade.